Differentiating Small Cell Carcinoma From Squamous Cell Carcinoma in Cytologic Specimens: A Head-to-Head Comparison of p40 and p63 Using Cell Block Immunocytochemistry. Issue 1 (January 2016) - Gailey, Michael P.; Bellizzi, Andrew M.; Jensen, Chris S.
Abstract : Distinguishing small cell carcinoma (SCC) from poorly differentiated squamous cell carcinoma (SCCA) can be challenging on fine needle aspiration (FNA). p63 immunocytochemistry is frequently used to support the presence of squamous differentiation. However, issues relating to specificity have arisen, and the common pan-p63 clone (4A4) has been challenged by antibodies specific for the ΔN isoform of p63 (p40), which show superior specificity for SCCA. A total of 50 SCC and 25 SCCA FNA cell blocks were stained with antibodies for p40, p63, K903, and CK5/6. For each marker, both extent and intensity of immunoreactivity were recorded, blinded to diagnosis, and H-scores (extent×intensity) were calculated. A total of 4%, 34%, 4%, and 2% of SCCs were positive for p40, p63, K903, and CK5/6, respectively. The rate of p63 positivity was significantly higher than for the other markers. Median H-scores in p63-positive SCCs (40) and SCCAs (270) were significantly different ( P <0.0001), though, and 94% of p63-positive SCCs showed an H-score <150. SCCs frequently express p63 (34%). In the SCCA versus SCC differential diagnosis, p40 and K903 are each marginally more sensitive (92%) than p63 (88%), whereas CK5/6 boasts the greatest specificity (98%). p63's poor specificity (66%) can be improved to 94%, if an H-score ≥150 is used as the cutoff for a positive result.